Computer algebra in scientific computing : 20th International Workshop, CASC 2018, Lille, France, September 17-21, 2018, Proceedings /: 20th International Workshop, CASC 2018, Lille, France, September 17-21, 2018, Proceedings. (2018) - Unknown
No abstract available